Navigating the complex terrain of political discourse: a multidimensional review and future pathways - Sun, Aina; Subramaniam, Vijayaletchumy (Human Resource Management Academic Research Society, 2023)
This paper offers an exhaustive review of political discourse studies, emphasizing its multifaceted nature by exploring four primary perspectives: pragmatics-oriented linguistics, critical discourse analysis, cognitive processes, and cultural and rhetorical influences. Beginning with a delineation of political discourse, the paper retroactively delves into prior research from these perspectives, highlighting the advancements in understanding political discourse's complex nature. Despite these advancements, notable gaps persist in the literature. This study's significance lies in its synthesis of major political discourse research, underscoring the multidimensionality of the subject, pinpointing existing research voids, and advocating for future studies that merge theoretical insights with real-world implications. To further the comprehension of political discourse in a dynamic sociopolitical landscape, upcoming research endeavors should champion interdisciplinary collaborations and embrace innovative methodologies.